1990
DOI: 10.1136/jmg.27.8.519
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive epidermolytic palmoplantar keratoderma.

Abstract: Palmoplantar keratoderma (PPK) is a heterogeneous group of disorders. Epidermolytic PPK is a weli delineated autosomal dominant entity, but no recessive form is known. Here we report two sons of phenotypically normal, consanguineous, Arab parents with features suggestive of PPK. They presented with patchy eczematous skin lesions followed by PPK and raised serum levels of IgE. Skin biopsy from the keratotic lesions showed the features ofepidermolytic hyperkeratosis. Autosomal recessive inheritance is suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Localized epidermolytic hyperkeratosis, first described by Vorner 22 and Klaus et al, 23 demonstrated dominant inheritance and male‐to‐male transmission, which was later substantiated, 11,24,25 although the inheritance is said to be autosomal dominant. Some researchers 26 suggested the existence of an autosomal recessive form, but because of the high background frequency of consanguinity in Kuwait where the patients were observed and because of the possibility of gonadal mosaicism, the evidence for recessive inheritance is not strong in this small family. Epidermolytic PPK is probably one of the most common keratin diseases, with an incidence of at least 4.4 per 100,000 in Northern Ireland 19 .…”
Section: Clinical Repercussionsmentioning
confidence: 87%
See 2 more Smart Citations
“…Localized epidermolytic hyperkeratosis, first described by Vorner 22 and Klaus et al, 23 demonstrated dominant inheritance and male‐to‐male transmission, which was later substantiated, 11,24,25 although the inheritance is said to be autosomal dominant. Some researchers 26 suggested the existence of an autosomal recessive form, but because of the high background frequency of consanguinity in Kuwait where the patients were observed and because of the possibility of gonadal mosaicism, the evidence for recessive inheritance is not strong in this small family. Epidermolytic PPK is probably one of the most common keratin diseases, with an incidence of at least 4.4 per 100,000 in Northern Ireland 19 .…”
Section: Clinical Repercussionsmentioning
confidence: 87%
“…20,21 Localized epidermolytic hyperkeratosis, first described by Vorner 22 and Klaus et al, 23 demonstrated dominant inheritance and male-to-male transmission, which was later substantiated, 11,24,25 although the inheritance is said to be autosomal dominant. Some researchers 26 suggested the existence of an autosomal recessive form, but because of the high background frequency of consanguinity in Kuwait where the patients were observed and because of the possibility of gonadal mosaicism, the evidence SKINmed: Dermatology for the Clinician (ISSN 1540-9740) is published bimonthly (Jan., March, May, July, Sept., Nov.) by Le Jacq Communications, Inc., Three Parklands Drive, Darien, CT 06820-3652. Copyright ©2004 by Le Jacq Communications, Inc. All rights reserved.…”
Section: Histopathologic Connotationmentioning
confidence: 99%
See 1 more Smart Citation
“…EPPK is a genodermatosis with an autosomal dominant mode of transmission, ¢rst described by Voerner in 1901 (2), although there has been one report of an autosomal recessive case, perhaps due to consanguinity (35). To date, all cases of this disease map to the type I keratin gene cluster on chromosome 17q12-q21 (27) and have been found to be caused by mutations in sequences encoding the 1A rod domain segment of the keratin 9 gene (19).…”
Section: Discussionmentioning
confidence: 99%